(untitled) (Bangladesh Journal of Agriculture, 2022)
Indigenous communities of the Rowangchhari upazila mostly depend on ethnomedicine for their primary health care. The purpose of the present study was to document significantly distinguishable ethno-medicinal plants and their ethno- pharmacological applications among the Marma community of Rowangchhari upazila of Bandarban Hill District. In this study, interviews and group discussion were conducted from July 2019 to December 2021 to obtain ethno medicinal data from the local herbalist and elderly villagers. Simultaneously, medicinal plants were also collected and recorded from natural wild habitats as well as from local markets during the study period. Local/village doctors (Baiddays) were also consulted regarding the names and uses of traditional medicinal treatments. In this study, a total of 81 medicinal plant species under 76 genera and 42 families have been recorded and documented, which have been used for the treatment of different ailments. Plant species used by herbal practitioners are mostly herbs (38%) and the representative from Euphorbiaceae family contained the maximum species (8). The most frequent usage category of ailments reported was skin problems. The majority of the remedies were prepared from juice (38%) and leaves were the most frequently used plant part (42%). The most widely used medicinal plants included, Achyranthes aspera L., Terminalia chebula Retz., Abelmoschus moschatus Medik., Ageratum conyzoides L., Blumea balsamifera DC. and Centella asiatica (L.) etc. Bangladesh J. Agri. 2022, 47(1): 75-87